Transforming User Engagement: Awareness and Utilization of Information Sources At Sikkim University Library - M., Suresh Babu; Choudhury Das, Reshmi Deb (International Journal of Information Studies, 2026)
The study investigates how students, faculty, and researchers perceive and use the library’s resources and services. Using a descriptive research design, data were collected from 70 purposively selected respondents through a structured questionnaire, supplemented by library records and scholarly literature. Findings reveal high awareness and usage of print books (85.7% aware, 65.7% frequent users), but significantly lower engagement with digital resources only 60% were aware of online databases, and just 35.7% used them frequently. Research support services showed the widest gap: 55.7% awareness but only 20% frequ ent use. Key barriers include a lack of understanding (45.7%), insufficient digital training (40%), limited access to technology (31.4%), and complex online interfaces (25.7%). A chi-square test confirmed a statistically significant relationship between awareness and utilisation (÷² = 41.39, df = 3, p < 0.05). The study concludes that targeted awareness campaigns, mandatory digital literacy workshops, infrastructure upgrades, and user friendly interfaces are essential to bridge usage gaps. Strategic recommendations include integrating library training into the curriculum and improving discovery tools. Ultimately, the research underscores the need for a user centred approach to align Sikkim University Library’s evolving services with academic demands in the digital age, thereby enhancing accessibility, satisfaction, and scholarly support.